2001
DOI: 10.1029/1999rs002418
|View full text |Cite
|
Sign up to set email alerts
|

Verification of ionospheric sensors

Abstract: Abstract. Ionospheric products from sensors and models were compared to investigate strengths and limitations of each. Total electron content data from computerized ionospheric tomography (CIT) and TOPEX sensors in the Caribbean region in 1997 were compared to estimates produced by models Parameterized Ionospheric Model (PIM) and Raytrace/ICEDBent-Gallagher (RIBG) and global maps from GPS. A 5 total electron content unit (TECU) bias was observed in TOPEX. CIT and TOPEX confirmed the location and structure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…IDA4D has been well validated [Coker et al, 2001;Watermann et al, 2002; and used in a number of scientific investigations Bust and Mitchell, 2008;Garner et al, 2006;Yin et al, 2006;Mitchell et al, 2005]. IDA4D is an objective analysis data assimilation algorithm based closely on the Navy Research Laboratories meteorological 3DVAR algorithm [Daley and Barker, 2000].…”
Section: Ida4dmentioning
confidence: 99%
See 1 more Smart Citation
“…IDA4D has been well validated [Coker et al, 2001;Watermann et al, 2002; and used in a number of scientific investigations Bust and Mitchell, 2008;Garner et al, 2006;Yin et al, 2006;Mitchell et al, 2005]. IDA4D is an objective analysis data assimilation algorithm based closely on the Navy Research Laboratories meteorological 3DVAR algorithm [Daley and Barker, 2000].…”
Section: Ida4dmentioning
confidence: 99%
“…While validation of IDA4D has been performed [Coker et al, 2001;Watermann et al, 2002], these validations have either been comparisons against independent observations of TEC or case studies with ISRs. Recently, a long term multiple-month statistical analysis was carried out comparing in situ observations of electron density from the CHAMP satellite Plasma Languin Probe (PLP) instrument [Cooke et al, 2003] with IDA4D estimates of electron density that are interpolated in space and time onto the CHAMP observation points.…”
Section: Champ Validation Of Ida4dmentioning
confidence: 99%
“…IDA4D has been primarily used as a 3‐D electron density imaging algorithm. It has been well validated [e.g., Coker et al , 2001; Watermann et al , 2002] and applied to several scientific investigations, in particular, the investigation of the ionospheric response to major geomagnetic storms [ Bust et al , 2007; Bust and Mitchell , 2008], including the formation and evolution of storm enhanced density (SED).…”
Section: Datamentioning
confidence: 99%
“…The horizontal resolution obtainable with CIT arrays can be as small as a few kilometers, while experimental investigations [Watermann et al, 2002;Coker et al, 2001] have demonstrated that the vertical resolution is $20-50 km (limited by the minimum elevation angle). When used in this fashion, CIT represents an inexpensive unique data source that provides high resolution spatial imaging of the ionosphere.…”
Section: Beacon Cit Datamentioning
confidence: 99%